TRENDS IN ROAD SAFETY IN UZBEKISTAN (American Journal of Interdisciplinary Research and Development, 2023)
Road safety has always been under the special attention of the government of Uzbekistan. Since 1991, when Uzbekistan became independent, more than 100 laws and by-laws related to road safety, traffic rules, training and education, vehicle inspection, insurance, etc. have been adopted. It should be recognized that there are common legal frameworks, road design standards, vehicle design specifications and road safety management frameworks. As in many countries, the question arises whether these documents are up to date and how these laws are implemented in practice.